ChemInform Abstract: Catalytic Water Oxidation by Ruthenium Complexes Containing Negatively Charged Ligand Frameworks. Issue 23 (May 2016) - Kaerkaes, Markus D.; Aakermark, Bjoern
Abstract: Review: 87 refs.